2018
DOI: 10.3390/molecules23102484
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Polysaccharides from Dendrobium officinale and Their Effects on Apoptosis of HeLa Cell Line

Abstract: Dendrobium officinale is a widely used medicinal plant in China with numerous bio-activities. However, the main structure and anti-tumor activity of the polysaccharides from this plant have not been investigated. In this study, we elucidated the main structure of polysaccharides purified with DEAE and Sephadex G-25 from Dendrobium officinale grown under different planting conditions. In addition, the anti-tumor activity was tested via MTT assays. The results showed that the polysaccharides of Dendrobium offici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…e protein in the polysaccharides was removed using the Sevage method [20] three to five times until no white floccules were evident at the border between the water and chloroform to obtain DOP. e degradation of DOP with different molecular weights was evaluated by the method our group used for the long term [18] but with slight differences. 3.6 g of DOP was dissolved in 314.7 mL of distilled water in an ultrasonic bath.…”
Section: Extraction and Degradation Of Dops With Different Molecular mentioning
confidence: 99%
See 1 more Smart Citation
“…e protein in the polysaccharides was removed using the Sevage method [20] three to five times until no white floccules were evident at the border between the water and chloroform to obtain DOP. e degradation of DOP with different molecular weights was evaluated by the method our group used for the long term [18] but with slight differences. 3.6 g of DOP was dissolved in 314.7 mL of distilled water in an ultrasonic bath.…”
Section: Extraction and Degradation Of Dops With Different Molecular mentioning
confidence: 99%
“…Zhao et al degraded polysaccharides from Porphyra haitanensis using the H 2 O 2 system to obtain fragments of different molecular weights and proved that the antioxidant activity of them was closely related to the molecular weight [16]. However, in terms of DOPs, some studies applied polysaccharides by fractional precipitation or the total polysaccharides to investigate the antitumor activity [17,18], and fewer reports have published concerning polysaccharides that degraded into a series of molecular weights but lacking comparison of molecular weights [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to Chinese medicine theory, (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale clears heat and nourishes the lung, thereby treating lung-related diseases and improving the overall life quality of patients with lung cancer [29]. In modern pharmacological studies, (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale has displayed significant bio-active functions, including immunomodulatory [30,31], antioxidant [32,33], anti-inflammatory [34], antitumor [35,36] and hepatoprotective functions [37]. To date, most of the research in this area has been focused on polysaccharides and extracts from (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale , but flavonoids are a widespread group of significant substances with various biological pharmacological functions [38].…”
Section: Introductionmentioning
confidence: 99%
“…The structure-activity relationship study, including also quercetin for comparison, demonstrated that the presence of a methoxyl group in C6 of the A ring of flavonol patuletin enhanced its anticancer potential [28]. Yu et al have purified polysaccharides from the stem extract of the medicinal plant Dendrobium officinale grown under different planting conditions (in the greenhouse and in the wild) and compared their structure and antitumor properties on HeLa cells [29]. Polysaccharides showed a significant activity only after oxidative degradation to smaller molecular weight species.…”
mentioning
confidence: 99%
“…Polysaccharides showed a significant activity only after oxidative degradation to smaller molecular weight species. The fractions from wild plants showed an evident antiproliferative and pro-apoptotic activities while the effects of the fractions from greenhouse plants were not significant [29]. Nguyen et al have biotransformed three selected anthraquinones into their O-glucoside by a bacteria glycosyltransferase, and tested these products for their antiproliferative affects against various cancer cells (AGS: gastric; HeLa: cervical; Hep-G2: liver) [30].…”
mentioning
confidence: 99%